A theropod track assemblage including large deinonychosaur tracks from the Lower Cretaceous of Asia. (October 2016) - Xing, Lida; Lockley, Martin G.; Klein, Hendrik; Peng, Guangzhao; Ye, Yong; Jiang, Shan; Zhang, Jianping; Persons, W. Scott; Xu, Ting
Abstract: A total of more than 40 tridactyl and didactyl tracks were preserved as natural casts on four fallen blocks of sandstone representing the Lower Cretaceous Jiaguan Formation of Gulin County in southeastern Sichuan Province, China. While several trackways can be distinctly followed, others are isolated imprints only. All have been flattened by overburden pressures. Tridactyl tracks are present with three size-classes being <10 cm, 10–20 cm and >20 cm in length. Morphologically they are similar to the ichnogenus Eubrontes, considering the relatively weak mesaxony. Eight of the tracks on one of the blocks are clearly didactyl and are here interpreted as representing large and medium sized dromaeosaurids. The largest track is about ∼30 cm long and comparable in size to the type of Dromaeopodus (∼28 cm), from the Lower Cretaceous of Shandong Province, which was the largest dromaeosaurid track previously reported. This report adds new data to the growing number of dromaeosaurid tracksites reports from China, and from the Jiaguan Formation, suggesting that this theropod group had a preference for fluvial paleoenvironments.